Pharmacogenetic Basis of Response Fluctuations to Methotrexate in Rheumatoid Arthritis: A Narrative Review - Qaisrani, Mehwish Nawaz; Farhat, Kulsoom; Noor, Mudassar (Current Rheumatology Reviews, 2025)
Rheumatoid arthritis is a crippling autoimmune disease affecting more than 18 million people worldwide and thus becoming one of the important contributors to the global health burden. The majority of the affected are females, especially those above the age of 50, but males and younger adults are equally vulnerable. It is a constellation of genetic and environmental factors that interplay to manifest the joint deformities and disabilities that are the hallmarks of this disease. Painkillers are used alongside disease-modifying anti-rheumatic drugs to minimize the patient’s agony and also to halt the progression of the disease. Worldwide, methotrexate is recommended as the first-line drug, but unexpected resistance is encountered in a significant number of patients. This review summarizes the pathophysiology, clinical findings, and therapeutic strategies for rheumatoid with a focus on research studies performed to establish a genetic basis for response fluctuations of methotrexate across different population groups.
Keywords: response fluctuations